Оценка некоторых особенностей горного производства - Кобылянский, Борис Борисович (НТУ "ХПИ", 2015)
На современном этапе технического развития все комплексные системы промышленного производства и в частности угольной промышленности, требуют автоматизации всего процесса включающего работу добычного и транспортного оборудования, что нельзя выполнить без детального математического описания всех специфических явлений характеризующих конкретное производство. Поэтому, для решения задачи управления сложными технологическими, многофакторными системами, предлагается использование непараметрической статистики, которые в отечественной специальной литературе не нашли должного отражения.

At the present stage of technical development all the complex system of industrial production and particularly the coal industry, requires automating the entire process including the work of mining and transport equipment, which can not be done without a detailed mathematical description of specific phenomena characterizing the specific production. Therefore, to solve the problem of managing complex technology, multifactorial systems, provided the use of non-parametric statistics, which are in the national literature is not adequately reflected. Nevertheless, it is such mathematical approaches allow to perform a correct forecast of the phenomena in question beyond the available experimental data sufficient to solve the most practical problems with accuracy, especially in those cases where the number of the data is relatively small.
Assessment some particularly mining production
Keywords: угольная промышленность; оценка; непараметрическая статистика; критерий; coal industry; assessment; nonparametric statistics.